Chinese species of Pediobius Walker (Hymenoptera: Eulophidae) - Cao, Huan-Xi; Salle, John La; Zhu, Chao-Dong (Zootaxa, 2017)
The Chinese species of Pediobius Walker, 1846 are treated in this paper, resulting in 34 species, of which 5 are newly described: P. bisulcatus Cao & Zhu sp. n., P. elongatus Cao & Zhu sp. n., P.petiolapilus Cao & Zhu sp. n., P. prominentis Cao & Zhu, sp. n., and P. tortricida Cao & Zhu, sp. n. Nine species are also newly recorded from China: P. anomalus (Gahan, 1920), P. bethylicidus Kerrich, 1973, P. bruchicida (Rondani, 1872), P. cassidae Erdös, 1958, P. claviger (Thomson, 1878), P. erionotae Kerrich, 1973, P. phragmitis Bouček, 1965, P. saulius (Walker, 1839), and P. tetratomus (Thomson, 1878). Four new synonyms are proposed: P. illiberidis Liao, 1987 under P. pyrgo (Walker, 1839) syn. n., P. planiceps Sheng & Kamijo, 1992 under P. inexpectatus Kerrich, 1973 syn. n., P. sinensis Sheng & Wang, 1994 under P. facialis (Giraud, 1863) syn. n., and P. songshaominus Liao, 1987 under P. yunanensis Liao, 1987 syn. n. The species-group concept is used to compare similar species, of which eight are recognized in China including two newly recognized groups: the cassidae-group and the crassicornis-group. One species complex, the P. eubius complex, is also recognized. An updated checklist of the Chinese species of Pediobius is provided, with species-group placement. New host records for Pediobius species from China are summarized in a table and valid species possibly present in China but not included in this study in another table. A key to all known females and males of Chinese Pediobius is also provided.